2005
DOI: 10.1007/s10654-004-5961-5
|View full text |Cite
|
Sign up to set email alerts
|

Can the relation between tooth loss and chronic disease be explained by socio-economic status? A 24-year follow-up from the Population Study of Women in Gothenburg, Sweden

Abstract: The objective of this study was to evaluate the association between number of missing teeth and all cause, cardiovascular, and cancer mortality as well as morbidity and to explore whether socio-economic factors mediate this association. An ongoing prospective cohort study of 1462 Swedish women included a dental survey in 1968/69 with follow-up until 1992/93. The dental examination included a panoramic radiographic survey and a questionnaire. Number of missing teeth at baseline was analysed in a Cox proportiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
83
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(97 citation statements)
references
References 28 publications
10
83
4
Order By: Relevance
“…Similarly, positive association was recorded in previous reports [8,10], whereas Johansson et al [18] found that CHD patients had significantly higher numbers of periodontal pockets 4-6 mm and higher bleeding on probing (BOP).…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Similarly, positive association was recorded in previous reports [8,10], whereas Johansson et al [18] found that CHD patients had significantly higher numbers of periodontal pockets 4-6 mm and higher bleeding on probing (BOP).…”
Section: Discussionsupporting
confidence: 61%
“…Although many risk factors of CHD have been identified, a significant proportion of this pathological condition cannot be explained by those traditional risk factors [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Oral hygiene differs among certain races and ethnic groups, 7 with African-Americans reporting higher rates of unmet needs for oral health care. 8 Low socio-economic status is associated with tooth loss 9 and tooth decay. 10 Thus, the typical demographic and socio-economic profile of people who sustained SCI puts the majority at an increased risk for developing oral and dental problems.…”
Section: Introductionmentioning
confidence: 99%